2017
DOI: 10.1371/journal.pone.0174986
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate release in leachate from municipal landfills of central Poland

Abstract: Phthalate diesters (PAEs) are used as plasticizer additives to polymer chains to make the material more flexible and malleable. PAEs are bonded physically, not chemically, to the polymeric matrix and can migrate to and leach from the product surface, posing a serious danger to the environment and human health. There have been a number of studies on PAE concentrations in landfill leachate conducted in the EU and around the world, though few in Poland. In the present study, the leachate of five municipal landfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…According to this and other studies, DEHP, which was classified as a Category 1B reprotoxin by the European Union’s REACH legislation, is the most frequently observed PAE in LLs (Asakura et al 2004; Zhang and Wang 2009). Wowkonowicz and Kijeńska (2017) detected DEHP < 1.3 to 73.9 μg/L and DMP < 0.6 to 1.98 μg/L to 4.72 μg/L in LLs generated by an old cell located in central Poland. Kalmykova et al (2013) reported that DEHP concentrations in LL samples ranged from < 1.0 to 23 μg/L and that DEP concentrations ranged from < 0.10 to 22 μg/L, while DnOP and DnBP were not detected.…”
Section: Resultsmentioning
confidence: 97%
“…According to this and other studies, DEHP, which was classified as a Category 1B reprotoxin by the European Union’s REACH legislation, is the most frequently observed PAE in LLs (Asakura et al 2004; Zhang and Wang 2009). Wowkonowicz and Kijeńska (2017) detected DEHP < 1.3 to 73.9 μg/L and DMP < 0.6 to 1.98 μg/L to 4.72 μg/L in LLs generated by an old cell located in central Poland. Kalmykova et al (2013) reported that DEHP concentrations in LL samples ranged from < 1.0 to 23 μg/L and that DEP concentrations ranged from < 0.10 to 22 μg/L, while DnOP and DnBP were not detected.…”
Section: Resultsmentioning
confidence: 97%
“…Due to the unbound nature of the polymer, DEHP can easily leach from products (Pearson and Trissel 1993 ). DEHP pollutes the environment and is detected in samples from soil, indoor air, water, plants, and human foods (Tran et al 2017 ; Wowkonowicz and Kijeńska 2017 ). For the human population, the main source of DEHP for can be found in contaminated food with which DEHP comes into contact during the production process (Fierens et al 2012 ; Heinemeyer et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jonsson et al (2003) found PAEs in 11 of 17 landfill leachates analyzed in Europe [26], and Bauer et al (1997) in all the leachates analyzed from Bavarian landfills [24]. In leachates from landfill in Japan [25] and in Poland [28], PAEs were found in all the leachates measured, DEHP being found in the highest most concentrations. Gao and Wen (2016) also pointed out that DEHP concentrations were the highest, while DEP and DMP were presented in a relatively low concentration [29].…”
Section: Introductionmentioning
confidence: 95%